Processos constitutivos da docência superior: saberes e fazeres de professores de fisioterapia - Austria, Verônica Cardoso (2009)
This research is inserted in Line of Formation, Knowledge and Teacher Professional Development , of the Education Master s Degree at Universidade Federal de Santa Maria, and had as main goal to understand how occurs the constituent processes of higher education for teachers physiotherapists who acts in the Course of Physical Therapy, in the context of the Universidade Federal de Santa Maria, concerning the integration between the knowledge acquired in graduation and the knowledge of teaching higher. Of this goal result three specific objectives, that are: understanding how occurs the formation process of the teachers physiotherapists; recognize which knowledge the Physical Therapy s teachers mobilizes in their pedagogical action; understand how teachers physiotherapists narrate the integration between knowledge of the graduate to the knowledge necessary for teaching practice. The theoretical contribution was composed by studies that concerns of the theme Higher Education / University Pedagogy (Zabalza, 2004; Garcia, 1999; Lucarelli, 2004, 2008; Anastasiou, 2002, 2007; Anastasiou e Alves, 2003; Pimenta e Anastasiou, 2005; Tardif, 2002; Cunha, 2004; Bolzan, 2008; Isaia e Bolzan, 2004, 2006, 2007; Bolzan e Isaia, 2006, entre outros) and authors that treats of the Physiotherapy and its trajectory (Rebelatto e Botomé, 2008; Haddad et al., 2006; Andrade, Lemos e Dall Ago, 2006), among others. To achieve the goals, we conducted a search of the type qualitative narrative, whose tools of data collection were narrative interviews, realized from a guide of topics. The people were six teachers of the UFSM s course of Physiotherapy. Besides the interviews, we request each teacher to available the didactic material of their discipline, to complement the analysis of narratives. Made part of the analysis as the background, the Pedagogic Project of the course of Physiotherapy. Through the content analysis it was possible to build three categories. The strength of the graduation of physical therapist was characterized by elements that showed the importance attached to the practice of the profession for the teaching role, when the subjects showed a large appreciation of the professional knowledge, or when give prominence mobilizing elements of teaching, related to Physiotherapy. Challenges facing the teaching was marked by the recurrence of elements that showed the difficulties of the teachers in front of teaching performance, at the beginning of their career in this profession for which were not initially prepared, or at their continued exercise, when they reporting practices and concepts that courses to the traditional model of education. The category learning to be a teacher presented evidence narratives of a learning process teaching, demonstrating a capability in the teaching of these people in the direction of processes of teaching and learning that take into account the people learners, especially favored by DCN for courses of Physiotherapy (2002). We understand that the constitutive processes of the higher education, for teachers physiotherapists, occur in the entwine of knowledge of the profession and the knowledge learned of the and about teaching, which occurs across the course of trajectory oh these teachers. This process is stimulated when there is the possibility of sharing between people, so that the reflection on their actions promotes an awareness of them and thus its transformation.